Assessment of resection margins during breast-conserving surgery using multimodal optical coherence tomography - D. A. Vorontsov; E. V. Gubarkova; M. A. Sirotkina; A. A. Sovetskiy; S. N. Aleksakhina; T. T. Tabagua; E. A. Busko; E. N. Imyanitov; S. S. Kuznetsov; A. Yu. Vorontsov; E. V. Zagaynova; S. V. Gamayunov; et al. (Опухоли женской репродуктивной системы)
Background. Breast cancer (BC) has been ranked first in morbidity and mortality among the female population in Russian Federation for several years. Rapid and accurate intraoperative examination of the cleanliness of resection margins is the main condition for breast-conserving surgery (BCS) to reduce the risks of local recurrence.Aim. To examine the tumor margins and assess the cleanliness of the resection margins in BCS in patients diagnosed with BC using multimodal optical coherence tomography (MM OCT) with comparative planned histological and additional molecular genetic analysis.Materials and methods. The study was carried out on postoperative samples of tumor and non-tumor breast tissue obtained from 115 patients with BC T1–2N0M0G2–3 stage IA–IIA, after BCS in the volume of radical resection or lumpectomy with histological control of the resection margins. A spectral domain MM OCT device (OCT 1300-E, BioMedTech LLC, Russia) was used, which provides structural OCT images to study the backscattering properties of tissue and allows performing a quantitative assessment of the elastic properties of the tissue by compression optical coherence elastography (OCE).Results. The MM OCT method was able to determine the exact margins between the tumor and non-tumor breast tissue. The main signs of the tumor were a decrease in the level and depth of penetration of the OCT signal in the structural OCT images, as well as an increase in the stiffness values (>200 kPa) in the OCE images with the highest stiffness values (>600 kPa) in the area of tumor cell accumulations. The use of compression OCE made it possible to detect clusters of tumor cells in the margins of resection at a distance of 5 mm from the visible border of the tumor. Among the 132 studied resection margins in 6 cases, the positive resection margin was determined by the OCE method, which was subsequently confirmed histologically. The negative resection margins were characterized by the lowest stiffness values (<200 kPa) in the OCE images and were confirmed by both histological analysis and molecular genetic analysis. ROC-analysis established a threshold stiffness value of 159.8 kPa, which indicates the presence of tumor tissue at the resection margins in the presence of a high stiffness area larger than 500 µm. The high diagnostic accuracy of the OCE method (98.5 %) was determined to distinguish between the negative and positive resection margins during BCS.Conclusion. The use of MM OCT with OCE modality makes it possible to clearly distinguish different types of breast tissue in BC (adipose tissue, connective tissue, accumulation of tumor cells). MM OCT can be used as an additional intraoperative tool for visualizing tumor cells boundaries and assessing the cleanliness of resection margins in real time during BCS.